A study of neck injury arising from motor vehicle accidents and its clinical management. - Gurumoorthy, Dhakshinamoorthy (Curtin University, 1996)
The syndrome commonly referred to as whiplash injury" resulting from motor vehicle accidents is complex and remains a challenge to clinicians, as is evidenced by the recent report of the Quebec task force on the "whiplash syndrome". The main objective of this prospective randomised study was to evaluate two conservative treatment regimens (early immobilisation-experimental group-1, early active mobilisation experimental group-2) which are based on accepted physiological rationale and then to compare their effectiveness with existing treatment regimens that are commonly practiced (control group) in the management of "whiplash" type of injuries. To this stage, the current study is the only prospective randomised clinical trial of its type conducted with a sufficiently large sample size and over a long study period. The results of the current study clearly demonstrated that the subjects in the immobilised group recovered from their pain-related symptoms and returned to their normal duties sooner than those in the other two treatment groups. In addition to this, those subjects who received the immobilisation regimen did not show adverse effects on either the range of motion or the strength of the neck muscles. Thus, the immobilisation regimen was clearly shown to be the preferred option when compared to the other two treatment methodologies investigated in the current study.Although the primary interest of the current study was to compare the efficacy of three different treatment regimens, a series of statistical analyses were performed to establish the prognostic significance of several factors associated with "whiplash" injury. This showed that factors such as gender, age, speed of the vehicles involved, paraesthesia, intensity of pain at the time of the initial examination, interscapular pain, blurred vision and difficulty in focusing, all had prognostic value. Similarly, the type of collision, seating position, presence of headache within 24 hours post injury, pre-existing degenerative changes in the cervical spine, loss of lordosis and litigation factors had no prognostic significance. Another major emphasis of the current study has been to concentrate on the pain related symptoms of the neck which are of major concern to "whiplash" subjects and to those clinicians treating them. A paucity of such information is considered to be one of the most notable causes of difficulties encountered in the management of "whiplash" injuries.As an adjunct to the main study, the morphology of the deep pre- and post vertebral muscles of the neck region using embalmed cadavers and fresh post-mortem specimens was investigated, as the literature is deficient in--this regard. Similarly, a longitudinal study of 45 subjects was also performed using Magnetic Resonance Imaging (MRI) technology. The longitudinal nature of the M.R.I. study provided for the first time an account of the details associated with the progressive pathological changes that occurred in some disc lesions, at defined points in time following a MVA. The observations made from the adjunct studies help develop a better understanding of the pathoanatomy associated with the deep muscles of the neck region and the pathological changes that occur following a traumatic disc lesion as evidenced within 2 weeks, after 3 months and 12 months post- injury. On the basis of the observations made in the current study, a classification of the "whiplash" injury has been proposed for the consideration of clinicians. Similarly, the questionnaire used for data collection in the current study, can be readily modified and utilised in a clinical situation for establishing documentation, planning treatment strategies and for evaluation of the treatment outcomes of "whiplash" type of injuries.